A Comparative Study of High and Low Achievers and their Learning Styles at University Level’ - Ishtiaq, Asma; Mahboob, Shumaila; Rasool, Shafqat (Annals of Human and Social Sciences, 2023)
The purpose of this study is to examine the comparing between high and low achievers and theirs’ learning styles at university level and to find out different learning styles used by the students’ at university level and compare mean score high and low achievers to use different learning styles at university level. This current work was also focus on the students learning styles at university level which make them high and low achievers. The study was delimited to the perception of students for gain education by using different learning styles. Achievement of the students are depend on theirs’ prefer learning styles. And the teachers facilitate the students for achieving the new facts and figures. It included formal experiences. The researcher collected personally from students. The population of the study was G.C University Faisalabad. The result and conclusions was draw on the basis of data-Analysis questionnaire contain nine factors of the learning styles and 350 items. The research supervisor and other professors of faculty were consulted for the development and validation of questionnaire. The researcher visited all the sample departments personally. The questionnaire was distributed among respondents and gave them maximum time to fill in the questionnaire. After collection of data, it was tabulated, scored analyzed and interpreted by means of suitable statically by applying descriptive statics and t-test. Secondary information were also collected in this regard and compared to assess the probability and significant of the study.